Oxalic Acid Regeneration of Ceramic Filter Medium Used in the Dewatering of Iron Ore. (20th November 2012) - Salmimies, Riina; Kallas, Juha; Ekberg, Bjarne; Häkkinen, Antti
Abstract : The regeneration of the ceramic filter medium in the dewatering of iron ore enables the use of the medium for much longer periods in comparison to traditional filter cloths. The regeneration is commonly a combination of several techniques, of which one is the acid washing of the medium. Despite being effective against iron oxides, the phenomena related to the acid washing of the ceramic filter medium with oxalic acid have so far been less extensively published. The aim of this study was to investigate the dissolution of iron oxide particles from the surface of the filter medium and the consequent changes in the performance and in the structure of the medium. The dissolution of the particles was found to exhibit some kind of a steady state dependent on temperature but not so much on the acid concentration. Changes in permeability as well as in pore size were found to take place even after the dissolution of the particles had ceased.